Anticardiolipin and/or anti-β2-glycoprotein-I antibodies are associated with adverse IVF outcomes - Wu, Li; Fang, Xuhui; Lu, Fangting; Zhang, Yu; Wang, Yanshi; Kwak-Kim, Joanne (Frontiers in Immunology, 2022)
Objective: The purpose of the study was to evaluate the effects of anticardiolipin (aCL) and/or anti-β2-glycoprotein-I (aβ2GPI) antibodies, namely antiphospholipid antibody (APA), on in vitro fertilization (IVF) outcomes. Materials and Methods: The study group comprises infertile women with APA undergoing IVF/ET cycles. Controls were infertility women with tubal etiology without APA. The impact of APA on reproductive outcomes, such as oocyte quality, embryo quality, and implantation capacity, was compared between the study group and controls. Additionally, peripheral blood T cell immunity, such as T helper (Th)1, Th2, Th17, and T regualtory (Treg) cells, and cytokines were analyzed by flow cytometric. Differences between the study group and controls were analyzed by Results: A total of 132 infertile women, including 44 women with APA, and 88 controls were sequentially recruited for this study. Women with APA had lower numbers of total and perfect/available embryos and lower rates of MII oocytes, blastocyst formation, perfect and available embryos, implantation, clinical pregnancy, and take-home baby. Additionally, imbalanced Th1/Th2 and Th17/Treg ratios, significantly higher levels of serum IL-2, TNF-ɑ, IFN-γ, and IL-17A, and a significantly lower serum IL-4 were noticed in women with APA compared to controls. Conclusion: Women with APA such as aCL and/or aβ2GPI antibodies were associated with adverse IVF outcomes. Early screening for these antibodies, in particular aCL and aβ2GPI antibodies, and appropriate consultation for couples undergoing IVF should be considered. In addition, underlying immunopathology and inflammatory immune mechanisms associated with APA should be further explored.